The evolution and impact of tourism in the Mediterranean: the case of Island Regions, 1990-2002 - Manera, Carles; Garau, Jaume; Serrano, Eloi (Cuadernos de Turismo, 2016)
This paper aims to analyse one of the world’s top tourist destinations, the Mediterranean, and, more specifically, the evolution and impact of mass tourism on its western islands (Corsica, Sardinia, Sicily, Malta and the Balearic Islands) throughout the final decade of the 20th century. Firstly a general overview of world tourism is given, followed by an analysis of tourism in the Mediterranean. In continuation, an in-depth study is made of the evolution and impact of tourism on the aforementioned islands. Finally, possible signs of Dutch disease are examined in these island regions, since their economies have taken advantage of natural resources in the development of their tourist industries, but overspecialization might well jeopardize their future development.